2012
DOI: 10.1007/s10067-012-1973-9
|View full text |Cite
|
Sign up to set email alerts
|

The time-averaged inflammatory disease activity estimates the progression of erosions in MRI of the sacroiliac joints in ankylosing spondylitis

Abstract: A method to estimate the individual ankylosing spondylitis (AS) patient radiological progression of semi-quantitative magnetic resonance imaging (MRI) changes in the sacroiliac joints has not been described yet, which this study examines. Inflammatory disease activity and MRIs of the sacroiliac joints of 38 patients with recent onset established AS were analyzed at baseline and during follow-up. Sacroiliac MRIs were semi-quantitatively assessed using a modification of the "Spondylarthritis Research Consortium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…reported that although the role of T2W-STIR and CE-MRI are comparable in identifying the activity of AS, administration of contrast agents may be beneficial for inexperienced MRI readers or detecting early AS with minimal changes. [10] However, some studies using small sample had shown that DWI and CE-MRI had similar diagnostic value, and that CE-MRI does not contribute significant additional information as compared to DWI,[17181920] which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…reported that although the role of T2W-STIR and CE-MRI are comparable in identifying the activity of AS, administration of contrast agents may be beneficial for inexperienced MRI readers or detecting early AS with minimal changes. [10] However, some studies using small sample had shown that DWI and CE-MRI had similar diagnostic value, and that CE-MRI does not contribute significant additional information as compared to DWI,[17181920] which is consistent with our results.…”
Section: Discussionsupporting
confidence: 91%
“…Structural lesions at the SI joints are also readily detectable on MRI and are considered hallmark signs of manifest SpA, but little is known about the evolution of such lesions over time and their relationship to BME. Most studies that have investigated the association between MRI findings and SpA have been cross‐sectional , and the few longitudinal studies in the field have examined highly selected and mostly small sample sizes of SpA patients without inclusion of patients with non–SpA‐related LBP .…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies examining ESR are inconsistent . In AS a single study found strong correlation between time‐averaged CRP and spinal erosions but not spinal BMO . There is conflicting evidence of association between sacroiliac BMO and CRP …”
Section: Statementmentioning
confidence: 94%
“…37,38 In AS a single study found strong correlation between time-averaged CRP and spinal erosions but not spinal BMO. 41 There is conflicting evidence of association between sacroiliac BMO and CRP. 7,37,40 Symptom-based disease activity scores of axial SpA are not consistently associated with acute inflammation of the spine or SIJ.…”
Section: Statementmentioning
confidence: 99%